Penerapan Kontrak Yang Seimbang Antara Pekerja Rumah Tangga Dan Majikan - Fadli Anugrah,; Elvin Saputra; Sandri Merdiandi; Zainal Abidin; Ruli Nanda; Juniar Hartikasari (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
The presence of a contract between the parties is often associated with a balance in thecontract. However, the idea that the contract between the parties does not provide aposition balance for one of them will remain. Attempts to resolve imbalances incontractual relationships occur because such contracts are considered unfair andburdensome. One example of a contract imbalance is the employment relationship betweena housekeeper and an employer. Normative law research is the type of research used. Theauthor uses written documents, legislative regulations, and other related literature assecondary data sources. Article 1339 BW states that an agreement binding not only what isexpressly stipulated therein, but also everything that by its nature is required by justice,custom, or law to maintain a balance in the employment contract between the worker andthe employer.